Experimental study of torrefied pine as a gasification fuel using a bubbling fluidized bed gasifier. (August 2016) - Kulkarni, Avanti; Baker, Ryan; Abdoulmomine, Nourredine; Adhikari, Sushil; Bhavnani, Sushil
Abstract: Torrefied biomass has higher C/O ratio, resulting in improved heating value and reduced hygroscopic nature of the biomass, thus enabling longer storage times. In the southeastern United States, pine is has been identified as a potential feedstock for energy production. The objective of this study was to understand the performance of torrefied pine as a gasification fuel in a bench-scale bubbling fluidized bed gasifier. The gasification of torrefied pine was carried out at 790, 935 and 1000 °C and three equivalence ratios (ERs: 0.20, 0.25 and 0.30). The effect of process variables were studied based on i) products yield, ii) syngas composition iii) syngas energy content, and iv) contaminants. The mean concentration of CO increased with an increase in temperature, but was not statistically significant. On the other hand, H2 concentration increased whereas CH4 concentration decreased significantly with an increase in temperature from 790 to 935 °C. Further, with an increase in ER from 0.20 to 0.30, only CO2 concentrations increased in the syngas. Results from torrefied pine were compared with raw pine gasification, and it was observed that torrefied pine gasification led to much higher char yield (more than twice) than pine; however, it produced less than half as much tar. Highlights: A bench-scale bubbling fluidized bed gasifier was used for gasification. Effect of temperature and equivalence ratio was studied for torrefied pine. Torrefied pine gasification resulted in more char than using raw pine. Torrefied pine yield lower tar than raw pine under similar conditions.